Polyclonal spread of blaOXA-23 and blaOXA-58 in Acinetobacter baumannii isolates from Argentina - Andrea Karina Merkier; Mariana Catalano; Maria Soledad Ramirez; Cecilia Quiroga; Betina Orman; Laura Ratier; Angela Famiglietti; Carlos Vay; Ana Di Martino; Sara Kaufman; Daniela Centrón (Journal of Infection in Developing Countries)
Background: In order to study the enzymatic carbapenem resistance mechanisms in Acinetobacter baumannii isolates from Argentina, we performed molecular characterization on 41 epidemiologically unrelated strains isolated from 1995 to 2006 with diminished susceptibilities to imipenem and meropenem. Methodology: Acinetobacter baumannii isolates were identified with the ARDRA technique. The total genomic DNA was used to detect each carbapenem β-lactamase gene described so far in this species and those insertion sequences usually associated to carbapenem β-lactamase genes (ISAba1, 2, 3, 4 and IS18) by the PCR technique with specific primers. Results: 26 out of 41 Acinetobacter baumannii isolates with diminished susceptibilities to carbapenems harboured the blaOXA-23 gene. The blaOXA-58 was detected in 13 out of 41 isolates. ISAba1 was always located upstream blaOXA-23. All isolates containing the blaOXA-58 gene showed ISAba3 downstream of the carbapenemase, while 4 isolates had a second copy of the ISAba3 upstream of the gene. Conclusion: Enzymatic carbapenem resistance in Acinetobacter baumannii was found in 88% of 41 non-epidemiologically-related strains mediated by the polyclonal spread of the blaOXA-23 and blaOXA-58 genes. The genetic structures surrounding the oxacillinase genes found in our bacterial isolates revealed a particular epidemiology in our geographical region. This data suggests the need of local molecular surveillance to help control multirresistance Acinetobacter baumannii infections.